PENGARUH KOMITMEN ORGANISASIONAL DAN KOMITMEN PROFESIONAL TERHADAP KEPUASAN KERJA AKUNTAN PUBLIK DENGAN MOTIVASI SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Kantor Akuntan Publik Di Semarang) - Yusrina, 14.05.52.0071; Kartika, Andi (Students' Journal of Accounting and Banking, 2018)
The purpose of this study aims to determine the effect of organizational commitment and professional commitment to job satisfaction auditor moderated by motivation. This research uses a quantitative approach with descriptive method. Technique of collecting data is done through questioner observation. The population of this research is the public accounting firm in Semarang who is willing to accept and fill out the questionnaire. Samples taken as many as 10 KAP of the overall KAP in the city of Semarang. Motivation can be interpreted as an internal and external impulse in a person indicated by the desire and interest, encouragement and need, hope and aspiration, respect and respect. Motivation is what makes a person act. From these definitions motivation can be done by satisfying their need to participate in organizational goals in a creative and free environment. The results showed there was a positive and significant influence between organizational commitment, professional commitment and motivation to the job satisfaction of an auditor. With motivation is a moderation variable. Keywords: Organizational Commitment, Professional Commitment, Motivation and Job Satisfaction.